First record of parasitism by Hepatozoon (Miller, 1908) (Apicomplexa: Hepatozoidae) in anurans from the Caatinga, Brazil. - Costa de Carvalho, Carla Adrielle (2024)
The aim of this study was to register for the first time parasitism by Hepatozoon (Miller, 1908) in two species of bufonid anurans in areas of the Caatinga in Brazil, and to present morphometric analysis on the parasites and parasitized erythrocytes. During helminthological studies on anurans from the Brazilian Caatinga in 2019, blood smears of three specimens Rhinella diptycha (Cope, 1862) and three of Rhinella granulosa (Spix, 1824) in the municipality of Petrolina, state of Pernambuco, Brazil were analyzed. To make blood smears, blood samples were collected intracardiacally or through puncturing the ventral abdominal vein. The smears were analyzed under a light microscope at 1000x magnification. Morphometric dimensions of host cells and parasites were measured. The only parasite forms encountered in the blood of the two anuran species were intraerythrocytic gametocytes of Hepatozoon spp., only parasitizing erythrocytes, which had a hypertrophied appearance. Two distinct morphotypes of Hepatozoon were found: one in each host species and both of them different from morphotypes previously described and registered in Brazil. Therefore, the present study constitutes the first report of Hepatozoon sp. in anurans in the Caatinga biome, and also forms the first register of parasites of this genus in R. granulosa in this country.